2019
DOI: 10.1080/13691457.2019.1592122
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and social work with children and adolescents

Abstract: This article aims to alert social work researchers and practitioners to the importance of engaging in research and debate about how to approach and understand ADHD among children in general and locked-after children in care in particular. Social work researchers have largely been absent from academic discussions about the 'ADHD epidemic' despite the fact that the prevalence of ADHD diagnosis and medication is very high in child welfare populations. The social work profession can make important contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Some parents had voluntarily placed these children in care as they found this to be the safest option for the child. This reflects other research, which has shown that children with ADHD and ASD are over-represented in residential care (Buescher, et al., 2014; Dein, et al., 2021; Karlsson and Lundström, 2021). There are some protective factors to these placements.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some parents had voluntarily placed these children in care as they found this to be the safest option for the child. This reflects other research, which has shown that children with ADHD and ASD are over-represented in residential care (Buescher, et al., 2014; Dein, et al., 2021; Karlsson and Lundström, 2021). There are some protective factors to these placements.…”
Section: Discussionsupporting
confidence: 87%
“…The National Institute for Health and Care Excellence (NICE) guidelines on ADHD management suggest that children with this condition should only be prescribed medication if they have severe impairments that have adverse impacts on their daily lives (NICE, 2019). The social worker should play a key role in this area as they are the ones who work closely with LAC and have a unique, privileged insight into their individual daily needs (Karlsson and Lundstr€ om, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is a recognised disability in Sweden, and is accorded the same rights as all other disabilities. What makes ADHD an even more interesting lens for this study is the evidence of it being overrepresented among socioeconomically disadvantaged groups (Karlsson and Lundström 2021).…”
Section: Students With Disabilities In Higher Education: Barriers and Facilitatorsmentioning
confidence: 98%
“…The higher usage of mental health services for Lac could be a contributory factor to the ndings detailed in the Mandell et al (2008) study. Medication prescription and usage has been noted as high in the Lac population in several studies (19,104,105). The number of children aged between 0-5 years who had been prescribed medication raises some concern.…”
Section: Adverse Outcomes For the Lac With A Nddmentioning
confidence: 99%